2013
DOI: 10.1016/j.annemergmed.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Intravenous Ketorolac Versus Intravenous Metoclopramide Plus Diphenhydramine for Tension-Type and All Nonmigraine, Noncluster Recurrent Headaches

Abstract: Objective We compared metoclopramide 20 mg IV, combined with diphenhydramine 25 mg IV, to ketorolac 30 mg IV in adults with tension-type headache and all non-migraine, non-cluster recurrent headaches. Methods In this ED-based randomized, double-blind study, we enrolled adults with non-migraine, non-cluster recurrent headaches. Patients with tension-type headache were a subgroup of special interest. Our primary outcome was a comparison of the improvement in pain score between baseline and one hour later, asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…In prior studies, parenteral opiates were given to 25–60% of these patients 3,16,17 . Multiple expert reviews have reported that opiates should not be used as first-line therapy for migraine headaches in the ED or clinic 9,21–24 .…”
Section: Introductionmentioning
confidence: 99%
“…In prior studies, parenteral opiates were given to 25–60% of these patients 3,16,17 . Multiple expert reviews have reported that opiates should not be used as first-line therapy for migraine headaches in the ED or clinic 9,21–24 .…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous ketorolac was also compared with intravenous diphenhydramine plus metoclopramide for treatment of some primary headaches. The study concluded that for adults who presented to an ED with non-migraine, non-cluster primary headaches, intravenous diphenhydramine plus metoclopramide have better efficacy than intravenous ketorolac (27). Using a standard measuring tool like VAS and the precise selection of patients can be considered as the strengths in this study.…”
Section: Discussionmentioning
confidence: 99%
“…IV metoclopramide has been shown to be effective in the treatment of acute migraines when compared with sumatriptan, 22,24 hydromorphone, 25 prochlorperazine, 23 and ketorolac. 26 Its use should be considered as early therapy in the treatment of acute migraines.…”
Section: Discussionmentioning
confidence: 99%